2020
DOI: 10.1038/s41467-020-14625-1
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the aetiology of snoring from observational and genetic investigations in the UK Biobank

Abstract: Although snoring is common in the general population, its aetiology has been largely understudied. Here we report a genetic study on snoring (n~408,000; snorers~152,000) using data from the UK Biobank. We identify 42 genome-wide significant loci, with an SNPbased heritability estimate of~10% on the liability scale. Genetic correlations with body mass index, alcohol intake, smoking, schizophrenia, anorexia nervosa and neuroticism are observed. Gene-based associations identify 173 genes, including DLEU7, MSRB3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
103
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 80 publications
7
103
1
Order By: Relevance
“…17 Due to the importance of sleep in human health, there is growing interest in understanding the determinants of sleep-related traits and their relationships with other health conditions. Previous studies have reported associations between tobacco smoking, alcohol consumption, and body mass index with an increased risk of snoring; 15 insomnia and an increased risk of depression, diabetes, and cardiovascular disease; 16 longer sleep duration with an increased risk of breast cancer in women 19 and shorter sleep duration with a higher risk for myocardial infarction. 20 Nonetheless, most of these studies lack the design principles to perform causal inferences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Due to the importance of sleep in human health, there is growing interest in understanding the determinants of sleep-related traits and their relationships with other health conditions. Previous studies have reported associations between tobacco smoking, alcohol consumption, and body mass index with an increased risk of snoring; 15 insomnia and an increased risk of depression, diabetes, and cardiovascular disease; 16 longer sleep duration with an increased risk of breast cancer in women 19 and shorter sleep duration with a higher risk for myocardial infarction. 20 Nonetheless, most of these studies lack the design principles to perform causal inferences.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 More recently, genome-wide association studies (GWAS) have achieved considerable progress in the characterisation of the genetic architecture of sleep-related traits. [12][13][14][15] GWAS have identified 351 genomic risk loci associated with chronotype, 13 41 genomic loci associated with snoring, 15 and 202 genomic loci associated with insomnia. 16 Furthermore, significant genetic overlap with other conditions has been uncovered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genome-wide significant findings from these studies and the corresponding associations our study are found in Supplementary Table 1. Largerscale GWAS studies have been performed on OSA-related phenotypes such as snoring 16 . However, knowledge about OSA predisposing genetic loci is thus far limited 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this this version posted September 30, 2020. ; https://doi.org/10.1101/2020.09.29.20199893 doi: medRxiv preprint for snoring we previously published (26) . FinnGen GWAS results for sleep apnoea and snoring were obtained from the open access FinnGen resource ( http://r3.finngen.fi/ ).…”
mentioning
confidence: 99%